2008
DOI: 10.1016/j.ypmed.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and calcium intake in relation to risk of endometrial cancer: A systematic review of the literature

Abstract: Objective-In response to a recent ecologic study of UV exposure and endometrial cancer incidence, we present the epidemiologic evidence on the relation between intake of vitamin D and its metabolically related nutrient, calcium, and the occurrence of endometrial cancer.Methods-We conducted a systematic literature review and meta-analysis of vitamin D and calcium in relation to endometrial cancer, including peer-reviewed manuscripts published up to May 2007. Random and fixed effects summary estimates were compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 26 publications
2
26
2
Order By: Relevance
“…However, a recent meta-analysis of three case -control studies showed no relation between dietary vitamin D intake and endometrial cancer (McCullough et al, 2008). This can probably be explained by sunlight being the most important source of vitamin D, most diets being low in Vitamin D. In this meta-analysis, the highest intake category was 244 to 476 IU per day (McCullough et al, 2008), which is much less than the recommended 2000 IU per day ). An ecological study produced an estimated overall reduction in cancer mortality of 20% for Western European women living below the 59th latitude and of 9% for women in the United States if they were all given a daily dose of 1000 IU vitamin D .…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…However, a recent meta-analysis of three case -control studies showed no relation between dietary vitamin D intake and endometrial cancer (McCullough et al, 2008). This can probably be explained by sunlight being the most important source of vitamin D, most diets being low in Vitamin D. In this meta-analysis, the highest intake category was 244 to 476 IU per day (McCullough et al, 2008), which is much less than the recommended 2000 IU per day ). An ecological study produced an estimated overall reduction in cancer mortality of 20% for Western European women living below the 59th latitude and of 9% for women in the United States if they were all given a daily dose of 1000 IU vitamin D .…”
Section: Discussioncontrasting
confidence: 54%
“…It has been suggested that if a cell become malignant, 1,25-dihydroxy Vitamin D can induce apoptosis and prevent angiogenesis, thereby reducing the potential for the malignant cell to survive (Holick, 2006). However, a recent meta-analysis of three case -control studies showed no relation between dietary vitamin D intake and endometrial cancer (McCullough et al, 2008). This can probably be explained by sunlight being the most important source of vitamin D, most diets being low in Vitamin D. In this meta-analysis, the highest intake category was 244 to 476 IU per day (McCullough et al, 2008), which is much less than the recommended 2000 IU per day ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin A, D, antioxidants, calcium, folate nutraceuticals still remain a choice as cancer preventive supplements [176][177][178].…”
Section: Cancers In the Human Body And Nutraceutical Protectionmentioning
confidence: 99%
“…In other recent reports the investigators showed a positive response of different nutraceutical supplements and foods in cancer prevention of different organs in the body as shown in Table 3 with nutraceuticals and references. Bone cancer soy isoflavones [5] Breast cancer lycopene, phytoesterogen [122][123][124][125][126][127][128][129][130][131][132] Common cancer cruciferous vegetables [25,184] Colon cancer nuts, fibers [158][159][160][161][162][163][164][165][166][167][168][169][170][171][172] Gastric cancer herbs [173][174][175] Intestinal cancer sphingolipids [64,65,176] Liver cancer silbinin, citrous flavonoids [25] Lung cancer vitamins A and E [154][155][156][157] Ovary cancer Vitamin A, D, antioxidants [176][177][178] Pancreatic cancer Vitamins and isoflavones …”
Section: Cancers In the Human Body And Nutraceutical Protectionmentioning
confidence: 99%